TITIK TEMU ANTARA VOTING DAN SYURA DALAM PEMILIHAN PEMIMPIN DI INDONESIA PERSPEKTIF HUKUM TATA NEGARA ISLAM - Srimadona Srimadona; Sulastri Caniago (Institut Agama Islam Negeri Batusangkar, 2022)
This article discusses the position of voting and shura based on constitutional concepts in Indonesia and Islam and how the meeting point between voting and shura in the election of leaders in Indonesia from the perspective of Islamic constitutional law. Using a qualitative approach, this study finds that in a country that adheres to a democratic political system, voting is used to make very important state decisions, such as to elect representatives of the people or to elect a new leader. Voting can be done if consensus is not reached then it can be done by voting (voting). In Islam, shura means deliberation where decisions have to be made in deliberation. In Indonesia, shura is contained in the 4th principle of Pancasila which reads